Pyrazole and its Derivatives: Chemistry and Biological Importance - Meshram, Pooja S.; Thombre, Kalyani R.; Gupta, Krishna R.; Umekar, Milind J. (Mini-Reviews in Organic Chemistry, 2025)
Currently, the main focus of research is to develop disease treatment strategies that are both more safe and more effective. Nitrogen-containing 5-membered heterocyclic pyrazole is a unique scaffold in pharmaceutical development. Because of its remarkable diversity in biological activities, pyrazole and its derivatives have become a prominent scaffold that has attracted the interest of medicinal chemistry researchers. Researchers have developed pyrazole as a multipurpose lead compound for effective pharmacological activities. They have demonstrated a wide range of biological and pharmacological activities, including antidiabetic, antiparkinsonian, antitumor, analgesic, anti-inflammatory, antimicrobial, antitubercular, antileishmanial activity, and neuroprotective properties. Many scientists have improved and developed new structural alternatives as a result of this logical variation in the physiological reaction pattern and much more effective pharmacological interventions. This review presents a detailed overview of the literature work reported by researchers on pyrazoles and reports recent efforts made on this moiety. This has been followed by an in-depth analysis of the pyrazole concerning its medicinal significance. This follow-up may help medicinal chemists generate new leads possessing pyrazole nuclei with high efficacy. It is crucial for earlier research and projects that aim to investigate the diverse activities of compounds linked to pyrazole and its derivatives in the near future. This overview summarizes the introduction, design, and biological activity of pyrazole derivatives as antimicrobial, anticancer, antiviral, antitubercular and antimalarial agents.
Keywords: antiviral